α-C(sp3)-H Arylation of Cyclic Carbonyl Compounds - Wang, Mei; Wang, Wei; Li, Dashan; Wang, Wen-Jing; Zhan, Rui; Shao, Li-Dong (Natural Products and Bioprospecting, 2021)
α-C(sp3)-H arylation is an important type of C-H functionalization. Various biologically significant natural products, chemical intermediates, and drugs have been effectively prepared via C-H functionalization. Cyclic carbonyl compounds comprise of cyclic ketones, enones, lactones, and lactams. The α-C(sp3)-H arylation of these compounds have been exhibited high efficiency in forming C(sp3)-C(sp2) bonds, played a crucial role in organic synthesis, and attracted majority of interests from organic and medicinal communities. This review focused on the most significant advances including methods, mechanism, and applications in total synthesis of natural products in the field of α-C(sp3)-H arylations of cyclic carbonyl compounds in recent years.